Grammatische und kognitive Anregungsprozesse beim Dialogischen Lesen mit inputoptimierten Bilderbüchern : Potentiale für die Sprachbildung mehrsprachiger Kinder in der Grundschule (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2025)
Dialogic reading (DR) promotes literacy, but its influence on L2 learners' grammar acquisition is under-researched. The article explores how special education students use DR with an input-optimised picture book to promote the grammar acquisition of multilingual primary school children before and after training. The analysis also highlights sustained shared thinking processes and the responsive behaviour that the students use to establish high quality input in DR.
Keywords: Dialogic reading; input-optimised picture books; grammar acquisition; input quality